Analisis Kemampuan Literasi Siswa di Sekolah Dasar pada Program Kampus Mengajar II di Kabupaten Sinjai - Amalia Putri, Indah; Supriadi, Supriadi; Erwin Nurdiansyah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
Abstract:This study aims to identify the barriers experienced by third-grade students at Public Elementary School 226 Saukangnge, Sinjai Regency, in developing reading literacy, as well as to examine the factors contributing to their reading difficulties. This research adopts a descriptive qualitative approach. The study was conducted at Public Elementary School 226 Saukangnge, located in Batu Belerang Village, Sinjai Borong Subdistrict, Sinjai Regency. The focus of the research includes reading literacy and the